2005
DOI: 10.1093/ps/84.3.454
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among prehatch and posthatch physiological parameters in early nutrient restricted broilers hatched from eggs laid by young breeder hens

Abstract: The objective of this study was to establish relationships among various physiological parameters in early (through 72 h posthatch) nutrient restricted broiler chicks from young breeder hens. Despite a 19% decrease in mean BW between 0 and 72 h posthatch, there were no chick mortalities. Liver glycogen peaked at 24 h, and peaks in rectal temperature, plasma glucose, and plasma refractive index occurred at 48 h. By 24 h, negative correlations were noted between BW and relative liver weight and between liver gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 38 publications
0
14
0
2
Order By: Relevance
“…Consequently, the various developmental phases of broilers have been physiologically adjusted for rapid growth and muscle accretion (Jackson and Diamond, 1996). Understanding the intricate relationships of growth and physiological characteristics of broilers between the various developmental phases, such as the embryonic and early, mid-, and late-post-hatch periods may be critical in adjusting environmental factors to achieve maximal productivity (Bamelis et al, 2005;Peebles et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the various developmental phases of broilers have been physiologically adjusted for rapid growth and muscle accretion (Jackson and Diamond, 1996). Understanding the intricate relationships of growth and physiological characteristics of broilers between the various developmental phases, such as the embryonic and early, mid-, and late-post-hatch periods may be critical in adjusting environmental factors to achieve maximal productivity (Bamelis et al, 2005;Peebles et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…bational oxygen (Onagbesan et al, 2007;Celen et al, 2009) and CO 2 concentrations Onagbesan et al, 2007;Willemsen et al, 2008), incubation length (van de Ven et al, 2011), and incubational egg weight loss (Peebles et al, 2005) on broiler embryogenesis and posthatch growth and developmental characteristics. Previous scientists have examined relationships of the physiological characteristics of broilers within the embryonic or posthatch periods.…”
Section: Introductionmentioning
confidence: 99%
“…From these results, it is observed that early feeding is able to improve bird performance, since it provides lower initial weight loss reflecting in greater weight uniformity at 21 days of age (Sklan, 2001). However, this effect was not observed in the period from one to 42 days of age, confirming the authors who also did not find an advantage in the use of this supplementation in this period (Caregui et al, 2005;Pedroso et al, 2005;Peebles et al, 2005). Batal and Parsons (2002) observed that the weight gain in the one to 21-day-old period of birds that consumed neonatal supplementation within the 24-hour post-hatch period was the same as that of birds that did not consume this supplement, and the worst weight gain was observed for those birds that went through the 48 hour fast.…”
Section: Resultsmentioning
confidence: 60%
“…The existence of relationships between incubation temperature (Lourens et al, 2005;Yalcin et al, 2005;Hulet et al, 2007;Leksrisompong et al, 2007;Molenaar et al, 2011a;Willemsen et al, 2011) and relative humidity (Bruzual et al, 2000a, b) on embryonic and post-hatch broiler development have been reported in earlier research work. Similarly, several researchers have previously suggested that set egg weight (Pinchasov, 1991;Vieira and Moran, 1999;Moran, 2007;Wolanski et al, 2007;Abiola et al, 2008), egg nutritional composition (Moran, 2007), yolk sac nutrient utilization by embryo (Murakami, 1992), eggshell temperature (Lourens et al, 2005;Molenaar et al, 2011b), incubational oxygen (Onagbesan et al, 2007;Celen et al, 2009) and CO 2 concentrations (Everaet et al, 2007;Onagbesan et al, 2007;Willemsen et al, 2008), incubation length (van de Ven et al, 2011), and incubational egg weight loss (Peebles et al, 2005) may also have an effect on broiler embryogenesis and post-hatch growth and development. In many of the studies discussed earlier, an examination of the influence of various treatments imposed during incubation on overall broiler post-hatch performance was limited to within 48 h post-hatch. In a companion article, effects of pre-hatch physiological variables such as egg internal temperature and eggshell water vapor conductance on the posthatch broiler growth and performance of corresponding chicks through 3 d of age were presented by Pulikanti et al (2012b).…”
Section: Introductionmentioning
confidence: 89%
“…An in-depth understanding of the relationships between pre-and post-hatch physiological variables is critical for the improvement of broiler incubational and post-hatch grow out management practices so as to achieve optimal broiler processing yield (Bamelis et al, 2005;Peebles et al, 2005). Therefore, the current experiment was conducted on progeny from a Ross 708 broiler breeder flock, to examine specific relationships of egg and embryonic variables, such as embryonated egg internal (air cell) temperature (T emb ), incubation length (IL), G H2O , specific G H2O (g H2O ; G H2O adjusted to a 100 g set egg weight basis) and G H2O constant (K H2O ), with broiler growth and developmental characteristics through the middle and late terms of the post-hatch grow out period.…”
Section: Introductionmentioning
confidence: 99%